Value delivery in green consumption: the effect of advertisement value proposition on consumer perception and purchase intention - Zhang, Yan; Liu, Jiaqi; Li, Xiaoyong (Frontiers in Psychology, 2024)
This study investigates the value delivery process in green consumption following the service-dominant logic (S-D logic). The proposed framework explores the impact of firm value propositions and consumer value perceptions on consumer behavior, and its validity is tested through a survey-based experiment consisting of 589 responses. The findings underscore the role of advertising as a communication tool for firms to convey value propositions to consumers.Believability of advertising emerges as a key driver of value perceptions, and its influence is moderated by temporal framing. Specifically, future framing, which involves consumers in value creation, enhances emotional value perceptions, while past framing which highlights firms' commitment to environmental protection promotes environmental value perceptions. Consumer purchase intention primarily derives from value propositions and perceptions and could mutually benefit consumers, firms, and the environment.